The Effect of Police Oversight on Crime and Misconduct Allegations: Evidence from Chicago - Rivera, Roman G.; Ba, Bocar A. (The Review of Economics and Statistics, 2026)
Does police oversight increase crime? Studies examining this relationship often rely on major scandals as shocks, but the simultaneous effect of public outrage on officer behavior and crime contaminates the results. Using a framework distinguishing oversight and outrage, we identify two events that increased oversight but elicited no public reaction. We find that despite a subsequent decline in reported misconduct, these oversight increases likely did not significantly impact crime or officer activity, suggesting oversight can reduce misconduct without increasing crime. However, a major policing scandal likely increased crime but did not increase arrests and decreased stops and uses of force.